의학 강의의 질 개선을 위한 동영상 수업 분석 및 그 활용도 연구 - 백선용(Sunyong Baek); 임선주(Sun Ju Im); 이선희(Sun Hee Lee); 감비성(Beesung Kam); 윤소정(So Joung Yune); 이상수(Sang Soo L (Korean journal of medical education, 2011)
Purpose: The lecture is a technique for delivering knowledge and information cost-effectively to large medical classes in medical education. The aim of this study was to analyze teaching quality, based on triangle analysis of video recordings of medical lectures, to strengthen teaching competency in medical school. Methods: The subjects of this study were 13 medical professors who taught 1st- and 2nd-year medical students and agreed to a triangle analysis of video recordings of their lectures. We first performed triangle analysis, which consisted of a professional analysis of video recordings, self-assessment by teaching professors, and feedback from students, and the data were crosschecked by five school consultants for reliability and consistency. Results: Most of the distress that teachers experienced during the lecture occurred in uniform teaching environments, such as larger lecture classes. Larger lectures that primarily used PowerPoint as a medium to deliver information effected poor interaction with students. Other distressing factors in the lecture were personal characteristics and lack of strategic faculty development. Conclusion: Triangle analysis of video recordings of medical lectures gives teachers an opportunity and motive to improve teaching quality. Faculty development and various improvement strategies, based on this analysis, are expected to help teachers succeed as effective, efficient, and attractive lecturers while improving the quality of larger lecture classes. KCI Citation Count: 12